Rasch Model Analysis of the Psychometric Properties of the Positive Mental Health Scale in Students - Noorellah Yousefi; Alireza Pirkhaefi (روانشناسی بالینی و شخصیت)
Introduction: Mental health encompasses more than just the absence of pathological symptoms or diseases; it also includes the presence of positive mental health indicators. The aim of the present study was to determine the psychometric properties of the Positive Mental Health Scale based on the Rasch model.Method: This study was quantitative and descriptive, focusing on the analysis of students' responses to the Positive Mental Health Scale, which is based on the Rasch model. Therefore, the study was psychometric in nature. The sample consisted of 609 students from Farhangian University in Tehran during the academic year 2021-2022. These students were selected through convenience sampling and completed the Positive Mental Health Scale.Results: The results of the exploratory factor analysis and parallel analysis indicated the presence of a dominant factor. Additionally, the confirmatory factor analysis corroborated the findings of the exploratory factor analysis. None of the items exhibited local dependence; therefore, the hypothesis that the scale is unifactorial was confirmed. Based on the Partial Credit Model (PCM), the values of the two Infit and Outfit indices ranged from 0.5 to 1.5, indicating a good fit of the scale items with the Rasch model. The item difficulty index was determined to be at a moderate level, ranging from -0.2008 to 0.1486. The results of the item characteristic curves indicated that all items demonstrated good suitability. Additionally, the scale exhibited measurement stability across different genders. No item differential interaction (DIF) was identified based on gender. The person-item reliability coefficient was 0.88, Cronbach's alpha was 0.86, and McDonald's omega coefficient was 0.84.Discussion and conclusion: The results of the study indicated that the Positive Mental Health Scale is a unidimensional instrument with favorable psychometric properties for assessing positive mental health in students. It can also be utilized to evaluate interventions in this area.